A Qualitative Research on the Experience of Haemodialysis in South Karnataka: Lived Experience of Persons undergoing Haemodialysis - Blessy Prabha Valsaraj; Shripathy M. Bhat; Ravindra Prabhu; Dinesh N. (Journal of Krishna Institute of Medical Sciences University, 2014)
Background: Any chronic illness puts a person and family at risk of long term suffering, financial depletion and burden on the caregiver. When it comes to chronic kidney disease (CKD), the sufferers have to be dependent on maintenance dialysis weekly twice or thrice that demands a lot of time and finances. Apart from that, they face physical symptoms of fatigue, anaemia, nausea, muscle cramps, fluctuating blood pressure and many other symptoms. They are asked to maintain a strict dietary, fluid and medication regimen in order to support the kidneys. Aims and Objectives: The current study aimed at exploring the lived experience of persons undergoing haemodialysis. Material and Methods: The study was conducted among ten patients undergoing maintenance dialysis who were diagnosed as having chronic kidney failure from the dialysis unit of Kasturba Hospital, which is a tertiary health care centre in South Karnataka. A qualitative approach with phenomenological research design was adopted. Data was obtained through interviews using a background proforma and semi-structured interview schedule. The data was analysed using Husserl's method. The transcripts were coded and analysed for common categories and themes were derived out of them. Results: The themes emerged at the end of the study were mental agony, physical limitations, coping, financial burden, lack of support, feelings towards the machine and dialysis, search for hope and betterment, spiritual coping, marital relationship and sexuality and uncertainty and fear of tomorrow. Conclusions: The authors conclude that the individual's life is centred on negatively oriented cognitions that can be modified with theoretically oriented interventions like cognitive behaviour therapy.